Endlose Kälte Witterungsverlauf und Getreidepreise in den Burgundischen Niederlanden im 15. Jahrhundert - Camenisch, Chantal (Wirtschafts-, Sozial- und Umweltgeschichte, 2015)
Human societies are highly affected by climatic and weather conditions. This is especially true for preindustrial times. In the present volume, the author reconstructs the climate in 15th century Burgundian Netherlands.